Factors influencing the performance of multidisciplinary working groups in delivering climate information services to agro-pastoralists in Senegal: Insights from structural topic modelling - Muriithi, Cyrus; Ouedraogo, Issa; Wilson, Nguru; Diouf, Latyr (International Center for Tropical Agriculture (CIAT), 2025)
This report evaluates the resilience of Senegal’s pastoral systems through improved Climate Information Services (CIS). The assessment covered pastoral communities in Ndame, Oudalaye, and Yarang Balante, examining CIS access, use, and the effectiveness of Multidisciplinary Working Groups (MWGs). Results show that pastoralists value CIS for managing drought, pasture scarcity, and livestock health risks, but major constraints limit impact. Low literacy, weak connectivity, gender disparities, and poorly localized or untimely forecasts reduce usability. MWGs play a critical intermediary role but face challenges related to resources, coordination, and sustainability. Pastoralists demonstrate strong adaptive practices, including transhumance and collective grazing, yet these remain fragmented. The core challenge lies in CIS delivery rather than demand. Enhancing impact requires co-produced, human-centered CIS embedded in pastoral realities. Key recommendations include localizing information, strengthening gender and youth inclusion, integrating CIS with livestock services, institutionalizing MWGs, and expanding digital and radio dissemination to support long-term adaptation.